Implementasi Metode Interpolasi Bicubic Modifikasi pada Proses Downsampling Citra - Ferdyansyah Wijaya; Reynard Saputra; Derry Alamsyah (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2016)
Downsampling process is used to reduce the image resolution by eliminating some pixels, so it will affect the quality of output image. To keep the quality, modified bicubic interpolation method is used in the downsampling process. Modified bicubic interpolation is a modification of bicubic interpolation with same quality and faster processing time. This paper will discuss about the implementation of modified bicubic interpolation method on the image downsampling process by computing 16 nearest pixel values on the input image to produce pixel values for output image. Modified bicubic interpolation is tested at 2 (two) image types, RGB and grayscale. Each type is consist of 2 (two) format, JPG and BMP. Experimental results show that the most stable output size is from JPG RGB with 300 – 400 KB range and from JPG grayscale with 0 – 50 KB range. The fastest processing time is from JPG RGB with 200 – 300 KB range and for the grayscale on 25% scale from JPG with 150 – 200 KB range, 50% scale from JPG with 0 – 50 KB range and 75% scale from BMP. The highest PSNR value is from JPG RGB with 100 – 200 KB range and from JPG grayscale with 0 – 50 KB range.